Theory of electric drive. Laboratory guide study aid - Zavyalov, V. M. specialist in the field of electrical engineering Professor of Tomsk Polytechnic University, Doctor of technical sciences 1974- (TPU Publishing House, 2017)
In the laboratory guide are guidelines for nine laboratory works for studying parameters, static and dynamic modes of different electric drives. The guidelines contain both traditional topics (objectives and tasks, brief theory extracts, program of experiments, technical data of testbenches, check questions, references) and additional use of computer for advanced studies of electromechanical processes in electric drives. The laboratory guide is intended for students of all forms of learning.